Neil John Maclean Health Sciences Library collection development response to the TRC Calls to Action related to health - Linton, Janice (University of Manitoba, Neil John Maclean Health Sciences Library, 2017)
The Truth and Reconciliation Commission’s Calls to Action were issued in June 2015. A few weeks later, plans were being made to bring together participants from the university’s Rady Faculty of Health Sciences as a first step in developing the Reconciliation Action Plan. Motivated by the initiative of the Rady Faculty of Health Sciences and Dr. Marcia Anderson’s inspiring introduction to the development of an organizational response by our faculty in health sciences education, an examination of the Neil John Maclean Library’s Indigenous Health Collection and activities to date was carried out. The TRC Calls to Action related to health (#18 to #24) were consulted to identify strengths and gaps in the collection. The uniqueness of this dedicated Indigenous Health Collection situated in an academic health sciences library and the Neil John Maclean Library’s longstanding commitment to supporting Indigenous health services, education, and research highlighted our role in supporting the recommendations made by the commissioners. To that end, the following table, outlining the responsiveness of the Indigenous Health Collection & Services, was further developed to serve as a checklist that can be used as an example by health libraries, organizations, and resource centres to assist in guiding our individual and collective responses to the Calls to Action.